AKTUALISASI DIMENSI SEJARAH DAN MAKNA MITOLOGIS PERTAPAAN PRINGGODANI SEBAGAI UPAYA PEMBANGUNAN PENDIDIKAN PARIWISATA BERBASIS MASYARAKAT - Akhmad Arif Musadad (PAEDAGOGIA, 2009)
The problems of research include: (1) how is the concept of history dimension and mythological meaning of Pertapaan Pringgadani tourist object?; (2) to what extent has the society developed the history dimension and mythological meaning of tourist object?; (3) what are the obstacles in developing the history dimension and mythological meaning of tourist object?; and (4) what measures do the government do in the society- based tourism education development in Blumbang Tawangmangu? This study was conducted in Tawangmangu, Karanganyar regency. This study belonged to a descriptive qualitative research using a single-embedded case study. The data sources employed were: informant, place and event, as well as written source. The data were analyzed using an interactive analysis method. The result of research showed: (1) according the surrounding people, Pertapaan Pringgodani in Kaling Empire time was a place where a hermit defeated Prabu Boko; (2) in addition to physical development, the surrounding people always hold mondosio ritual up to now, as the expression of their gratitude; (3) the development of Pertapaan Pringgodani area has not been optimal. It is due to many obstacles such as heavy area, lack of supporting fund, and society’s low awareness; (4) in order to improve the society's awareness, the government conducts society empowerment and improvement of supporting infrastructures.